Upaya Guru dalam Menumbuhkan Literasi Membaca Siswa di MIM 11 TPAY Blimbing - Widianto, Suheri; Asriyah, Lina (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This research aims to describe the efforts made to foster reading literacy among students at MIM 11 TPAY Blimbing, identify the supporting factors for the implementation of the reading literacy program at MIM 11 TPAY, and examine the inhibiting factors in its execution. This study employs a qualitative descriptive method, with the research site located at MIM 11 TPAY Blimbing, Paciran, Lamongan. The subjects of this research were identified through interviews and observations. The findings indicate that the implementation of the literacy movement at MIM 11 TPAY Lamongan progresses through phases of habituation, development, and learning. Supporting factors at MIM 11 TPAY Blimbing, Paciran, Lamongan include the library, reading books, magazines, reading corners, and active reading posters. Conversely, the inhibiting factor identified is the library's suboptimal functionality due to students' poor reading habits.